2008
DOI: 10.1136/jramc-154-01-07
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management at Floor Level: A Comparison of Tracheal Intubation using the Macintosh and Airtraq Laryngoscopes

Abstract: Practitioners providing pre-hospital care during civilian practice and on military operations may be required to perform airway management and tracheal intubation at floor level. It has been shown that intubation using the Airtraq laryngoscope is easier to learn than standard Macintosh laryngoscopy. We hypothesised that the Airtraq would be easier to use and have shorter intubation times than Macintosh intubation. Sixty volunteers attending a medical conference with no prior Airtraq experience, who were skille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…On the other hand, as the students expressed in the questionnaires, they thought that the use of the Macintosh was the most difficult of all, and it also led to higher complication expectations compared to the others. Also this was in line with previous studies, where Airtraq was the most preferred instrument by the users in comparison with the Macintosh laryngoscope (17,18). In a comparison for anaesthetized adult patients with Manual in Line Axial Stabilization, the Airtraq group had a significantly longer duration for both intubation and laryngoscopy, although the Airtraq provided an equal success rate of intubation as the Macintosh laryngoscope (19).…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, as the students expressed in the questionnaires, they thought that the use of the Macintosh was the most difficult of all, and it also led to higher complication expectations compared to the others. Also this was in line with previous studies, where Airtraq was the most preferred instrument by the users in comparison with the Macintosh laryngoscope (17,18). In a comparison for anaesthetized adult patients with Manual in Line Axial Stabilization, the Airtraq group had a significantly longer duration for both intubation and laryngoscopy, although the Airtraq provided an equal success rate of intubation as the Macintosh laryngoscope (19).…”
Section: Discussionsupporting
confidence: 77%
“…Airtraqguided tracheal intubation was found to be faster and had lower rates of oesophageal intubation when compared with use of the Macintosh laryngoscope in a model of difficult intubation [18] and when managing the airway at floor level [19]. Tong et al [19] found significant differences in success rate between the Airtraq (tube mounted with 90°anti-clockwise rotation) and Macintosh laryngoscopes in a standard manikin at floor level. The use of the Airway Scope, in a study designed to simulate restricted access to the airway, resulted in a shorter time to intubate and ventilate compared with the Macintosh laryngoscope [26].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently stated reasons for this preference were quality of view and ease of use. Other studies have cited operator preference for either the Airtraq [18,19] or the Airway Scope [11] over the Macintosh laryngoscope. This is, however, the first study comparing the two indirect laryngoscopes when used by paramedics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations